Pengaruh Service Excellent Petugas Check In Counter Terhadap Kepuasan Penumpang Maskapai Citilink Di Bandar Udara Internasional El Tari Kupang - Maria Tiara Putri Manafe; Fryda Fatmayati (Lembaga Pengembangan Kinerja Dosen, 2023)
In the era of globalization, good service in accordance with expectations can provide satisfaction for passengers because service quality has a close relationship with passenger satisfaction. In general, the level of passenger satisfaction depends on the quality of service received. Various ways are done to be able to attract the hearts of passengers to feel satisfied with what they expect. The purpose of this study was to find out whether service excellence has an effect on Citilink airline passenger satisfaction. This study used quantitative methods, with data collection techniques using questionnaires. Questionnaires were distributed to passengers who had experienced Citilink airline services at El Tari Kupang International Airport. The respondents of this research were 100 respondents. In this study using the SPSS application to process data, this research uses Simple Linear Regression. The results of hypothesis testing show that Ho is rejected and Ha is accepted with a significant value (sig) of 0.000 and a calculated T value of 8.700. Because the sig value is 0.000 <0.05 and the calculated T value is 8.700 > 1984 T table, it means that there is an influence between variable X on variable Y. The results of simple linear regression analysis show that the magnitude of the influence of variable X excellent service on variable Y is passenger satisfaction of 43, 6% while the other 56.4% is influenced by other factors outside the X variable (excellent service).